The role of procedure simplification in improving citizen satisfaction: - بركات حيان; خير بك باسل (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This paper studies the role of simplifying procedures through continuous redesigning and updating to meet the citizen’s desires and keep up with with changes in laws and regulations, and being clear, not repeated and limited to what gives added value to the paperwork, as well as how important the mechanism in which this service is offered for the citizen in terms of providing means and information that give the citizen a clear image of how the service is offered and the time needed to achieve citizen’s satisfaction. A questionnaire has been distributed to a sample of 50 citizen who visited the Citizen’s Service Centre in the Municipality of Lattakia Governorate to obtain the required services over the period of five days at the rate of ten questionnaire per day. All the questionnaire are collected, SPSS statistical software is utilized to analyses data, the researcher findo offers a moral relationship and a strong connection between the up-to-date, clear and short procedures using simple forms to obtain and the citizen’s satisfaction . Meanwhile, no moral relationship is found between the availability of means and information required to offer those services and the citizen’s satisfaction. Accordingly, the researcher recommended the necessity of updating the procedures for the conduct of citizens’ transactions and reducing their number as much as possible, preparing guides explaining the procedures for each transaction in a clear and accurate manner, simplifying the approved forms for obtaining the service, and canceling external approvals to obtain the service in a way that reduces the effort and cost that the citizen should bear and improves his satisfaction.